1981
DOI: 10.1021/j150610a005
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation mechanism of excited acridine in nonreactive solvents

Abstract: excitation is believed to involve the = 0 -*• 1 transition and thus is a measure of the fundamental vibration for the ion.3 Although ion-matrix electronic interactions are on the order of 1 eV,22 differences in interactions between ground and excited vibrational states are probably small, and vibrational spectra of matrix-isolated molecular ions are believed to be representative of the gaseous ion. The fact that argon-krypton matrix differences are small (5-7 cm"1) for such ions as CF3+ and CHBr2+, which are o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

15
79
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(94 citation statements)
references
References 8 publications
15
79
0
Order By: Relevance
“…As shown in Figure 3, nitrate does not absorb significantly to the red of ∼320 nm, and so the radiation transmitted by the 340 nm filter should not excite that molecule directly. However, as shown in Figures 1 and 3, both neutral and protonated acridine do absorb strongly in the 300-400 nm region (38). This suggests the interesting possibility that the long-wavelength deprotonation might be due to acridine acting as a photosensitizer (39), transferring energy to nitrate anion which then reacts.…”
Section: Discussionmentioning
confidence: 93%
“…As shown in Figure 3, nitrate does not absorb significantly to the red of ∼320 nm, and so the radiation transmitted by the 340 nm filter should not excite that molecule directly. However, as shown in Figures 1 and 3, both neutral and protonated acridine do absorb strongly in the 300-400 nm region (38). This suggests the interesting possibility that the long-wavelength deprotonation might be due to acridine acting as a photosensitizer (39), transferring energy to nitrate anion which then reacts.…”
Section: Discussionmentioning
confidence: 93%
“…This will extend the sensory abilities of the compounds. Acridine has been much investigated since the mid-twentieth century and many of its properties have been the subject of a number of monographs [12,37] and more recent original papers [see, e.g., [38][39][40][41][42][43][44]). We have included acridine in the list of compounds discussed here with the goal of analyzing the changes in their spectral-luminescent properties and photophysical processes depending on the nature of the substituent in position 9 of acridine.…”
Section: The Spectral-luminiscent Properties Of Acridine Compoundsmentioning
confidence: 99%
“…Triplet state formation [11][12][13], excited state reduction [14,15], and relaxation between excited ππ * and nπ * states [11,[16][17][18] were reported for different acridine derivatives. The triplet state formation in some of acridines takes place very efficiently, however, it has already been reported [10] that there is no evidence of triplet state population of DSA dyes.…”
Section: Resultsmentioning
confidence: 99%
“…These states were found to play a crucial role in the excited state relaxation of some acridine derivatives [11,[16][17][18]. In most cases, the nπ * state of acridines is slightly higher than the ππ * state, however, it was also suggested that positions of ππ * and nπ * states in aprotic solvents may be inverted [12,20,21].…”
Section: Resultsmentioning
confidence: 99%